2001
DOI: 10.1086/323189
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Volcanic Clouds in Their First Few Days of Atmospheric Residence: The 1992 Eruptions of Crater Peak, Mount Spurr Volcano, Alaska

Abstract: Satellite SO 2 and ash measurements of Mount Spurr's three 1992 volcanic clouds are compared with ground-based observations to develop an understanding of the physical and chemical evolution of volcanic clouds. Each of the three eruptions with ratings of volcanic explosivity index three reached the lower stratosphere (14 km asl), but the clouds were mainly dispersed at the tropopause by moderate to strong (20-40 m/s) tropospheric winds. Three stages of cloud evolution were identified. First, heavy fallout of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 22 publications
(35 reference statements)
3
79
0
Order By: Relevance
“…Thus, our results indicate that some volcanic plumes may not be overseeded with ice. Indeed, this has been directly observed in some volcanic plumes such as the 17 September 1992 eruption of Mt Spurr, where remote sensing measurements showed that ash mass dominated over ice mass (Rose et al, 2001). The current study suggests that immersion freezing, and therefore overseeding, may be dictated by the differences in the mineralogy of the crystalline material found in volcanic ash.…”
Section: Atmospheric Implicationssupporting
confidence: 64%
“…Thus, our results indicate that some volcanic plumes may not be overseeded with ice. Indeed, this has been directly observed in some volcanic plumes such as the 17 September 1992 eruption of Mt Spurr, where remote sensing measurements showed that ash mass dominated over ice mass (Rose et al, 2001). The current study suggests that immersion freezing, and therefore overseeding, may be dictated by the differences in the mineralogy of the crystalline material found in volcanic ash.…”
Section: Atmospheric Implicationssupporting
confidence: 64%
“…The proportion of fine ash involved in aggregation may be inferred from satellite observations of volcanic ash clouds (e.g., 1992 eruptions of Crater Peak, USA, Rose et al, 2001). In the first 30 minutes, >70 wt.% of erupted material falls out within 10s km of the volcano while in the next 24 hours another ~25 wt.% of total erupted mass falls out within 100s km to 1000s km dominantly through hydrometeor-enhanced aggregation of fine ash.…”
Section: Aggregation Within Ash Plumes: Conditions and Downwind Changesmentioning
confidence: 99%
“…Also no background correction was made for the Eyjafjallajökull samples as mentioned earlier. An additional important aspect is initial processes in the volcanic cloud that lead to growth by aggregation and rapid sedimentation of fine ash particles (Rose et al, 2001). Such processes could be of importance during sampling in the Eyjafjallajökull volcanic clouds because they were only 1-2 days old.…”
Section: Sulphur Dioxide Conversion Rate In Volcanic Cloudsmentioning
confidence: 99%
“…Large particles sediment quickly while very fine ash particles (<15 µm) have been found to have a residence time of days to weeks in the UT/LMS (Rose and Durant, 2009;Niemeier et al, 2009). During the first 24 h after an eruption a rapid decrease of the fine ash (<25 µm) content of the volcanic cloud have been observed, likely caused by aggregation into larger particles with higher settling velocities (Rose et al, 2001). After this initial phase, ash concentrations decrease more slowly together with concentrations of SO 2 .…”
mentioning
confidence: 99%